Tensile loading of model caisson foundations for structures on sand - Kelly, R; Byrne, B; Houlsby, G; Martin, C (2004)
The viability of multiple footing structures that use suction caisson foundations would be improved if the up-wind leg(s) could resist significant tensile loads. In the particular case of offshore wind turbines, large moments are applied at foundation level by the action of wind and waves on the structure. For a multiple footing structure the applied moment is resisted primarily by vertical reactions on opposing foundations. If a significant tension can be allowed at the upwind side, then the spacing of the foundations, and therefore the overall size of the structure, can be greatly reduced. Bye et al (1995) suggest that the tensile capacity of caissons is dependent on the rate of loading, compared to the rate of drainage of excess pore pressure beneath the caisson. To investigate this, model caisson tests were carried out in test beds made of two different gradings of sand. Whilst the ultimate capacity is large in both cases (and controlled by the cavitation of the pore fluid) the displacements required to mobilise the loads are large compared to the diameter of the footing. These displacements are of a magnitude that would cause serviceability problems. The experimental results suggest that the upwind footing should be designed for tensile loading no greater than (at most) the drained friction on the skirt. Copyright © 2004 by The International Society of Offshore and Polar Engineers.